Determinants of Lecturer Performance: The Role of Talent Management, Motivation, and Job Satisfaction - Arinda Damayanti; Rachmad Hidayat; Sri Rahayu (Majapahit Journal of Islamic Finance and Management, 2026)
This research was conducted to examine the impact of talent management, motivation, and job satisfaction on the performance achievements of lecturers at KH. Bahaudin Mudhary University, Madura. Utilizing a quantitative methodology, this study explores the extent to which effective human resource potential management and work stimulation drive productivity within the academic sphere. Data collected via questionnaires were analyzed to verify the influence of these variables, both individually and collectively. These findings are projected to serve as a basis for the university's strategic policies in optimizing talent development and lecturer welfare to strengthen institutional quality.